Yasco Horsman. Theaters of Justice: Judging, Staging, and Working Through in Arendt, Brecht, and Delbo. Stanford UP, 2010. 232 pp. - Peter Yang (Studies in 20th & 21st Century Literature, 2014)
Review of Yasco Horsman. Theaters of Justice: Judging, Staging, and Working Through in Arendt, Brecht, and Delbo. Stanford UP, 2010. 232 pp.
Keywords: theater; Hannah Arendt; Charlotte Delbo; Bertolt Brecht